Illegal Fee Practice In The Tourism Sector In The Madura Area From The Prespective Of Indonesian Society And Criminal Law - Effendi, Tolib; Windari, Rusmilawati; Lali, Peternus Marttua Siahaan (Dinasti Research, 2025)
The Indonesian government, through Presidential Regulation No. 87 of 2016, established the Illegal Fees Eradication Task Force to conduct prevention, coordination, planning, data collection, and eradication of illegal fees. However, this regulation does not provide a clear limitation on what constitutes illegal fees. Furthermore, the Indonesian Criminal Code (KUHPidana) does not explicitly mention the crime of illegal fees collection. There is a significant gap between the understanding of illegal fees from the perspective of Indonesian society and that of criminal law. What the public around tourist areas especially in the Madura region identifies as illegal fees often does not fall within the scope of existing criminal regulations. In particular, four criminal provisions Article 368 paragraph (1) of the Criminal Code and Article 12 letters e, f, and g of the Corruption Eradication Law of 2001 bear similarities to illegal fees collection but remain inapplicable to many social practices labeled as such. This research adopts a juridical-normative method to analyze the compatibility between the prevailing legal rules, legal norms, and principles. The study explores how social perceptions of illegal fees differ from legal definitions, aiming to clarify the legal ambiguity and identify the limitations in the current regulatory framework related to illegal fees collection.keyword: Tourism, Illegal Fees, Criminal Law